Application of information and communication technology in cultural heritage as a development resource: the example of the project Secession route Osijek-Subotica - Mičić, Marija (Oeconomica Jadertina, 2020)
The starting point of the text are different approaches that perceive ICT as an indispensable generally accepted trend in business, and which also introduce dynamic changes in the modern market-cultural tourist competition. In order to present more clearly the concept of cultural heritage as a marketable product, key elements of the cultural tourism industry will be discussed. The direct impact of the technological revolution on implementation of new operational modes adapted to new, fast and flexible generation of consumers within the sector of tourism will also be analysed. Aspects of ICT in cultural heritage as a development resource will be highlighted with a specific example of Art Nouveau cultural heritage through the S.O.S. Secession Tourist route Osijek - Subotica. The project is co-financed by European funds with the aim of developing and promoting a common cultural and tourist product based on secession. The importance of visual Art Nouveau identity as an integral part of local economic development and the associated application of ICT in project implementation will be presented.
Keywords: cultural heritage; tourism; information and communication technology (ICT); secession